PENGARUH PENGETAHUAN DAN PERSEPSI TERHADAP MINAT MENABUNG DI BANK SYARIAH DENGAN RELIGIUSITAS SEBAGAI VARIABEL MODERASI(STUSI KASUS PADA MAHASISWA FAKULTAS EKONOMIDAN BISNIS ISLAM IAIN KERINCI) - Ropendra Ropendra; Novi Mubyarto; Elyanti Rosmanidar (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the influence of knowledge and perception based on the Theory of Planned Behavior on the interest in saving in Islamic banks, with religiosity as a moderating variable among students of the Faculty of Islamic Economics and Business at IAIN Kerinci. This research employed a quantitative approach with an explanatory research design to test the proposed hypotheses. Data were collected through questionnaires distributed to 100 students as research respondents. The data used in this study were primary data analyzed using the Partial Least Square (PLS) method with the assistance of SmartPLS version 4.0. The data analysis included outer model testing consisting of convergent validity, discriminant validity, and composite reliability, as well as inner model testing using the R-Square value. The results indicate that knowledge has a positive and significant effect on the interest in saving in Islamic banks. Meanwhile, perception does not significantly affect saving interest. Furthermore, religiosity is able to moderate the effect of knowledge on saving interest positively and significantly, but religiosity is unable to moderate the effect of perception on saving interest in Islamic banks.